2020
DOI: 10.1038/s41598-020-71119-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of a lifestyle intervention on the prevention of type 2 diabetes in a middle-income country

Abstract: This study aims to assess the effects of a community-based lifestyle intervention program on the incidence of type 2 diabetes (T2D). For this purpose, three communities in Tehran were chosen; one community received a face-to-face educational session embedded in a long-term communitywide lifestyle intervention aimed at supporting lifestyle changes. We followed up 9,204 participants (control: 5,739, intervention: 3,465) triennially from 1999 to 2015 (Waves 1-5). After a median follow-up of 3.5 years (wave 2), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Major gains will likely achieve from public health strategies targeting incorrect diet, physical inactivity, and preventing or stopping cigarette smoking 32 . As a successful example, in a community-based study in Tehran, it was shown that family-school and community based educational sessions resulted in about 20% decrease incidence of metabolic syndrome during 6 years follow up 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Major gains will likely achieve from public health strategies targeting incorrect diet, physical inactivity, and preventing or stopping cigarette smoking 32 . As a successful example, in a community-based study in Tehran, it was shown that family-school and community based educational sessions resulted in about 20% decrease incidence of metabolic syndrome during 6 years follow up 33 .…”
Section: Discussionmentioning
confidence: 99%
“…This result may also pertain to the lack of medication interventions by NPHWs and no physician supervision. In contrast to this study, the effectiveness of behavioral lifestyle interventions was documented when accompanied by therapeutic interventions [49,50] and supervised by physicians [51,52]. Another reason for not observing an effect on cholesterol-related outcomes may be the short one-year period of the interventions.…”
Section: Assessing Cholesterol-related Resultsmentioning
confidence: 64%
“…The TLGS intervention resulted in 70% higher cessation rate after 3.6 years 14 . After nine years, no reduction in smoking prevalence was observed in nondiabetic participants 15 .…”
mentioning
confidence: 87%